Additions to the knowledge of hydnoid Steccherinaceae: Cabalodontia, Etheirodon, Metuloidea, and Steccherinum. (4th July 2021) - Westphalen, Mauro C.; Motato-Vásquez, Viviana; Tomšovský, Michal; Gugliotta, Adriana M.
ABSTRACT: The family Steccherinaceae includes genera with smooth, hydnoid, and poroid hymenophores, monomitic to dimitic hyphal systems, and generative hyphae with clamps or simple septa. Steccherinum is the largest genus in the family, with a worldwide distribution, and is characterized mainly by a dimitic hyphal system and presence of thick-walled encrusted cystidia. Species traditionally included in Steccherinum, however, have been transferred to other genera based on results of molecular phylogenetic analyses. Even though knowledge of Steccherinaceae has increased in the past few years, very little is known about the hydnoid species of the family, especially from the Neotropics. In this study, we present morphological and phylogenetic analyses on hydnoid specimens of Steccherinaceae collected in the Neotropics. Molecular data of nuc internal transcribed spacer region ITS1-5.8S-ITS rDNA (ITS) and portions of nuc 28S rDNA (28S), translation elongation factor 1-α ( tef1 ), and the largest subunit of RNA polymerase II ( rpb1 ) were obtained from Brazilian collections. Types and original collections were studied for morphological comparison. Samples we studied grouped in four different genera of Steccherinaceae: Cabalodontia, Etheirodon, Metuloidea, and Steccherinum . Three new neotropical species, Cabalodontia delicata, Etheirodon purpureum, and Steccherinum larssonii, are described. In addition, the new combinations Cabalodontia albofibrillosa and Metuloidea reniformis are proposed. The four genera presented in this study are compared and discussed in detail.